GASTROINTESTINAL TRACT, MICROFLORA AND IMMUNITY - T.S. Lazareva; F.F. Zhvaniya (Педиатрическая фармакология)
The article highlights the issues of microflora and immunity of gastrointestinal tract. It provides data on principle functions of normal flora, influence of different factors on colonizational resistance development of an organism. The interaction between intestinal microflora and immunity is shown. The article proposes main approaches to dysbacteriosis correction at gastrointestinal diseases and indicates the leading role of diet therapy in complex treatment of chronic intestinal diseases.Key words: children, intestinal tract, microflora, immunity, diet therapy.